Radiographic hip anatomy correlates with range of motion and symptoms in National Hockey League players - Larson, C. M.; Ross, J. R.; Kuhn, A. W.; Fuller, D.; Rowley, D. M.; Giveans, M. R.; Stone, R. M.; Bedi, A. (The American Journal of Sports Medicine, 2017)
Background: Hip disorders in athletes have been increasingly recognized. Purpose: To characterize radiographic hip anatomy for National Hockey League (NHL) players and correlate it with hip range of motion and hip symptoms and/or surgery. Study Design: Cross-sectional study; Level of evidence, 3. Methods: Fifty-nine professional hockey players (118 hips) with 1 NHL organization (mean age, 24.2 years; range, 18-36) prospectively underwent history and physician examination by 2 independent orthopaedic surgeons. Current or previous groin and/or hip pain or surgery was noted. Anteroposterior (AP) pelvis and bilateral Dunn lateral radiographs were obtained for all players with assessment of hip morphology by 2 blinded independent orthopaedic surgeons. Results: Good to very good reliability of radiographic assessments was noted (intraclass correlation coefficients = 0.749-0.958). Sixty-four percent of athletes had a positive crossover sign, while 86% and 60% had a positive posterior wall sign and a prominent ischial spine sign, respectively. Twenty-one percent of hips demonstrated dysplastic acetabular features (lateral center edge angle <25°). Eighty-five percent and 89% of hips demonstrated cam-type morphology based on alpha angle (>50° Dunn lateral) and head-neck offset, respectively. Good to very good reliability was noted for ROM assessments (intraclass correlation coefficient >0.69). Mean hip flexion was 107.4º ± 6.7º, and mean hip internal rotation was 26.1º ± 6.6º. Thirty-one percent of hips had a history of hip-related pain and/or surgery. Higher AP, Dunn lateral, and maximal alpha angles correlated with decreased hip internal rotation (P = .004). Greater AP alpha angle correlated with decreased hip extension/abduction (P = .025), and greater Dunn lateral and maximal alpha angle correlated with decreased hip flexion/abduction (P = .001). A positive posterior wall sign correlated with increased straight hip abduction, while other radiographic acetabular parameters were not predictive of range of motion. Only decreased hip external rotation and total arc of motion correlated with an increased risk for current or prior hip symptoms or surgery (P < .001). Conclusion: Hip anatomy in NHL players is characterized by highly prevalent cam-type morphology (>85%) and acetabular retroversion (>60%). In addition, acetabular dysplasia (21%) was relatively common. Greater cam-type morphology correlated with decreased hip range of motion, and a positive crossover sign correlated with increased hip abduction. Decreased hip external rotation and total arc of motion were predictive of hip-related pain and/or surgery